Penggunaan Metode Role playing Meningkatkan Nilai Ujian Akhir Mahasiswa Blok Profesionalisme Kedokteran - Luh Gede Sri Yenny; I Made Wandia (Warmadewa University, 2016)
Pendidikan profesionalisme kedokteran merupakan salah satu komponen kurikulum yang sangat penting dalam kurikulum pendidikan dokter. Pengembangan dan perbaikan modul Blok Profesionalisme Kedokteran merupakan jembatan untuk menghasilkan lulusan kedokteran yang mampu bersikap dan berperilaku professional. Pengembangan modul dapat dilakukan dengan berbagai cara salah satunya yaitu dengan menerapkan metode role playing. Penerapan metode role playing dilakukan pada Blok Profesionalisme Kedokteran 2012 dan dibandingkan dengan Blok Profesionalisme kedokteran 2011 dimana pada saat itu metode role playing belum diterapkan. Penelitian ini bertujuan untuk mengetahui apakah terjadi peningkatan nilai ujian akhir mahasiswa, jumlah lulusan dan motivasi mahasiswa untuk belajar mandiri. Didapatkan kelulusan yang lebih tinggi pada Blok Profesionalisme Kedokteran 2012 dibandingkan dengan Blok Profesionalisme Kedokteran 2011 yaitu 83.7%: 32.2%. Terdapat hubungan yang bermakna antara penggunaan metode role playing dengan nilai ujian akhir mahasiswa (p<0.05) dan dengan kelulusan (p<0.05). Sebagian besar mahasiswa merasa lebih termotivasi untuk belajar profesionalisme kedokteran (94.55%). Penggunaan metode role playing dapat meningkatkan nilai ujian akhir, jumlah lulusan dan motivasi mahasiswa untuk belajar mandiri Blok Profesionalisme Kedokteran 2012.Kata Kunci: role playing, profesionalisme kedokteran, pendidikan kedokteran.[Role Playing Increases Students’ Scores of Final Examination in the Block Medical Professionalism].Medical professionalism education is one of very important curriculum components in medical education. Development and improvement of the module of the Block Medical Professionalism are the bridge to yielding a good, capable and professional medical doctor. The development of the module can be conducted in various ways, one of which is by applying the method of role playing. Role playing method applied at Block Medical Professionalism of 2012 was compared to Block Medical Professionalism of 201in which role playing was not applied This research aimed to assess if there was increase of the result score of the students’ final test, total number of passing students, and students’ self motivation to study individually. The study results showed a higher number of passing students in medical professionalism block of 2012 as compared to medical professionalism block of 2011 (83.7% vs 32.2%). There was a significant correlation between role playing and the mean score of the students’ final test (p<0.05) and with the number of passing students (p<0.05). Most student felt more motivated to learn medical professionalism (94.55%). Application of role playing method can improve the final test score, total number of passing students, and students’ self motivation to study medical professionalism of 2012.Key words: role playing, medical professionalism, medical education.